Initial and landing impact acceleration with mountain bike suspension forks - Orendurff, M. S.; Smith, G. A. (Twenty-First Annual Meeting of the American Society of Biomechanics Clemson University, South Carolina September 24-27, 1997, 1997)
The purpose of this investigation was to determine the effect of rigid fork and suspension fork stiffness (resistance to axial compression) on impact acceleration at the axle and frame during initial contact, and upon landing over three bump sizes. DISCUSSION Suspension forks clearly reduced large impacts transmitted to the rider through the front wheel during initial contact with an obstacle. The increased acceleration at the axle on large bumps suggest that the suspension forks allow the front wheel to move more rapidly. It may be that with suspension forks the tire will more closely follow the surface than with rigid forks. The subsequent landing impact (P2) showed no differences between the suspension forks and the rigid fork. Although this was unexpected, there are many possible reasons why this result was obtained. Since a rider's mass would be accelerated upward on the initial contact, and then descend on the landing contact this may reduce the effectiveness of the suspension forks. The riders may also have been somewhat off balance upon landing, and this may account for the increased variability seen in the P2 acceleration. The characteristics of the obstacle at initial contact and landing contact are not identical. The force vector of the landing impact may be more vertical than on the initial impact, resulting in a bending moment at the fork rather than long-axis compression. Also, impact attenuation may be reduced on successive bumps. Since no reduction in peak acceleration was seen during landing impacts (P2), this is a possible area of focus for future developments in suspension fork performance.